Isolation and Identification of Fish Infected with Bacteria in Some Farms of Babylon in Iraq - Alftlawy, Zaid Basim Hameed; Emran, Faiza Kadhim; Al-Khalaf , Alaa K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Fisheries is one of the main sectors on which some countries are increasingly dependent. Filling the food gap is an important resource in the agricultural resource base, but it is one of the neighborhoods affected by the agricultural activities. The bacterial disease agents were isolated from aquaculture in the Babylon governorate, Iraq, during December 2021 to the end of October 2022. A total of 65 specimens of Cyprinus carpio were infected (53%). Four bacterial diseases were diagnosed by clinical signs that appeared from severe infections of external and internal organs (fin rot, dropsy, bacterial gill disease, and vibriosis). Bacteria were identified according to their morphological characterization and using the Vitek 2 system, and they include Aeromonas sobria, A. hydrophila, A. veronii, Streptococcus thoraltensis, Serratia ficaria, Serratia fonticola, Serratia odorifera, and Vibrio cholerae. The results of the current study showed that the emergence of diseases in fish farms may be related to stress factors that fish suffer from as a result of dryness and scarcity of water, water quality, or the possibility of bacteria transfer either from water to fish or vice versa, or by handling.